The Effect of Green Marketing, Sustainable Market Research, and Consumer Engagement on Brand Loyalty and Consumer Legitimacy in MSMEs in Indonesia - Mendrofa, Kristiurman Jaya (International Journal of Business, Law, and Education, 2024)
The purpose of this study is to examine how consumer involvement, sustainable market research, and green marketing strategies affect brand loyalty and customer legitimacy in Micro, Small, and Medium-sized Enterprises (MSMEs) in Indonesia. Structural Equation Modelling (SEM) with Partial Least Squares (PLS-SEM) as the analysis approach was used in a quantitative analysis including 238 MSMEs from various industries and geographies. The study's sustainable practices have a strong positive correlation with both customer legitimacy and brand loyalty, according to the findings. The results underline the significance of sustainability in building legitimacy and loyalty among consumers as well as the mediating function that these practices have in influencing consumer views. Actionable insights for MSMEs, policymakers, and researchers are provided by the discussion of the practical and policy implications.